Anti‐angiogenic effects of CD73‐specific siRNA‐loaded nanoparticles in breast cancer‐bearing mice. Issue 10 (9th May 2018) - Ghalamfarsa, Ghasem; Rastegari, Ali; Atyabi, Fatemeh; Hassannia, Hadi; Hojjat‐Farsangi, Mohammad; Ghanbari, Amir; Anvari, Enayat; Mohammadi, Jamshid; Azizi, Gholamreza; Masjedi, Ali; Yousefi, Mehdi; Yousefi, Bahman; et al.
Abstract : CD73 facilitates tumor growth by upregulation of the adenosine (immunosuppressive factor) in the tumor microenvironment, however, its precise molecular mechanisms is not precisely understood. Regarding the importance of angiogenesis in tumor development and spreading, we decided to assign the anti‐angiogenic effects of CD73 suppression. We used chitosan lactate (ChLa) nanoparticles (NPs) to deliver CD73‐specific small interfering RNA (siRNA) into cancer cells. Our results showed that treatment of the 4T1 cells with CD73‐specific siRNA‐loaded NPs led to potent inhibition of cancer cell proliferation and cell cycle arrest, in vitro. This growth arrest was correlated with downregulation of angiogenesis‐related molecules including vascular endothelial growth factor (VEGF)‐A, VEGF‐R2, interleukin (IL)‐6, and transforming growth factor (TGF)‐β. Moreover, administration of NPs loaded with CD73‐siRNA into 4T1 breast cancer‐bearing mice led to tumor regression and increased mice survival time accompanied with downregulation of angiogenesis (VEGF‐A, VEGF‐R2, VE‐Cadherin, and CD31) and lymphangiogenesis (VEGF‐C and LYVE‐1)‐related genes in the tumor site. Furthermore, the expression of angiogenesis promoting factors including IL‐6, TGF‐β, signal transducer, and activator of transcription (STAT)3, hypoxia inducible factor (HIF)‐1α, and cyclooxygenase (COX)2 was decreased after the CD73 suppression in mice. Moreover, analysis of leukocytes derived from the tumor samples, spleen, and regional lymph nodes showed that they had lower capability for secretion of angiogenesis promoting factors after CD73‐silencing. These results indicate that suppression of tumor development by downregulation of CD73 is in part related to angiogenesis arrest. These findings imply a promising strategy for inhibiting tumor growth accompanied with suppressing the angiogenesis process. Abstract : The main objective of this study is to investigate the anti‐angiogenic potential of CD73‐specific siRNA‐loaded chitoan‐lactate nanoparticles in treatment of 4T1 breast cancer bearing mice.